Process for purifying and removing titanium from aluminum-silicon alloy flux
By using two flux spraying methods in the aluminum-silicon alloy, the first flux promotes the borolysis reaction of the titanium element and the second flux adsorption to remove TiB2 particles, the problem of unsatisfactory removal of titanium element in the prior art is solved, and an efficient and environmentally friendly titanium removal effect is achieved.
Patent Information
- Application Number
- CN202411535759.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-03-14
AI Technical Summary
The prior art is difficult to effectively remove titanium elements in aluminum-silicon alloys, and other impurities may be introduced, affecting the performance of the alloy.
The first flux spray method is adopted. The first flux contains sodium chloride, potassium chloride, potassium fluoride, potassium fluoride, potassium fluoride and potassium fluoroborate to promote the borolysis reaction of titanium elements; the second flux contains boron oxide, sodium carbonate and other components to adsorb and remove the resulting TiB2 particles.
The removal rate of titanium elements in aluminum-silicon alloys is significantly improved, the titanium content is reduced to the ideal range, and the introduction of other impurities is avoided, ensuring the improvement of alloy performance.
Smart Images

Figure CN119614934A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy refining and purification, relates to the refining and purification of aluminum alloys and the control of components such as titanium in the alloys, and specifically relates to a process for purifying and removing titanium from aluminum-silicon alloy flux. Background Art
[0002] Aluminum-silicon alloys are widely used in aerospace, automobile, electronics, new energy, construction, sports equipment, chemical industry and other fields due to their light weight, high strength, corrosion resistance, electrical conductivity and thermal conductivity. In the preparation process of aluminum-silicon alloys, the presence of titanium is an issue that needs attention. Due to the titanium dioxide or other titanium compounds that may be contained in the raw materials, aluminum-silicon alloys are prone to absorb titanium during the production of aluminum-silicon alloys by the molten salt electroeutectoid method, resulting in excessive titanium content. The excessive presence of titanium in aluminum-silicon alloys will have a significant negative impact on its performance, such as reducing the mechanical properties, corrosion resistance, casting performance, processing performance, electrical conductivity and thermal conductivity of the alloy. Therefore, optimizing the composition of aluminum-silicon alloys and reducing the titanium element in the ingot are of great significance for the application of aluminum-silicon alloys.
[0003] In order to reduce the titanium content in aluminum silicon alloys, researchers have conducted a lot of exploration and experiments. AbdulKhaliq et al. (Metallurgical and Materials Transactions B, 2021, 52: 3130-3141) disclose the introduction of aluminum-boron alloy to convert the titanium element in the aluminum melt into boride particles, and separate them from the aluminum melt by gravity sedimentation. Aluminum-boron alloy or boron-containing compounds are directly added to the aluminum alloy, so that the boron element therein reacts with the titanium-containing compound in the alloy to generate a titanium diboride phase, and the titanium diboride phase is deposited and removed by utilizing the characteristics that the density of the titanium diboride phase is higher than that of the aluminum alloy melt. However, the deposition removal method is not easy to operate in the production of aluminum alloys. A large amount of titanium-containing phases gather and segregate at the bottom of the molten pool, which is not easy to separate from the upper melt, making it difficult to stably control the titanium impurities in the product.
[0004] Although the traditional smelting and refining method can reduce the titanium content to a certain extent, the effect is not ideal and may introduce other impurity elements. Therefore, the development of an efficient and environmentally friendly titanium removal process has become an important issue in the field of aluminum silicon alloy preparation. Summary of the invention
[0005] The purpose of the present invention is to provide a process for purifying and removing titanium from aluminum-silicon alloy flux, so as to solve the problem that the above-mentioned traditional smelting and refining methods cannot ideally remove the titanium element in the aluminum-silicon alloy and may introduce other elements.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A process for purifying and removing titanium from aluminum-silicon alloy flux comprises the following steps:
[0008] (1) heating the titanium-aluminum-silicon alloy to be removed until it is uniformly melted to obtain a melt, and spraying a first flux into the melt using an inert gas to perform a first flux spraying process;
[0009] The first flux comprises the following components by weight percentage:
[0010] 7-11% sodium chloride, 9-14% potassium chloride, 7-11% potassium fluoride, 8-12% aluminum fluoride, 30-50% potassium fluoroborate, 8-16% sodium carbonate, 3-14% calcium fluoride;
[0011] (2) After the first flux is sprayed, the melt is stirred and kept warm and allowed to stand;
[0012] (3) After the melt is kept at a temperature and allowed to stand, an inert gas is used to spray a second flux, and a second flux spraying process is performed;
[0013] The second flux comprises the following components by weight percentage:
[0014] 20-26% sodium chloride, 26-34% potassium chloride, 9-13% potassium fluoride, 6-10% potassium cryolite, 12-16% boric oxide, 13-15% sodium carbonate;
[0015] (4) After the second flux is sprayed, the flux slag on the surface of the melt is scraped off to obtain an aluminum-silicon alloy melt;
[0016] (5) The obtained aluminum-silicon alloy melt is temperature-controlled and allowed to stand, stirred, filtered and cast to obtain a pure aluminum-silicon alloy after titanium is removed.
[0017] At present, since there is a certain amount of titanium in the raw materials for preparing aluminum-silicon alloys, the titanium content in aluminum-silicon alloy products increases, which has a series of adverse effects on the performance of aluminum-silicon alloys. In the prior art, the titanium element is removed by adding aluminum-boron alloy and heating it to melt, and precipitating it. However, due to the large amount of titanium-containing phases gathering and segregating at the bottom of the molten pool, it is not easy to separate from the upper melt, making it difficult to stably control the titanium impurities in the product. For example, invention patent 202310088205.9 discloses a method for adjusting the titanium content in aluminum-silicon alloy melts, adding aluminum-boron master alloys, potassium fluoroborate or borax and other boron-containing compounds to the aluminum-silicon alloy liquid, and smelting, adding refining agents and refining gases after smelting, and slagging after refining, thereby reducing titanium. In the above technology, after adding boron-containing compounds and then refining, the boronized titanium-containing phase is prone to precipitation, and the ordinary refining agent has limited adsorption effect on the titanium-containing phase. In view of the above problems, the present invention proposes a method of twice flux injection. First, the first flux injection adds boron-containing molten salt, and the mixed flux improves the boron element recovery rate and promotes its reaction with the titanium-containing phase. After the boronization reaction is fully completed, the second flux injection plays a role in adsorbing the titanium diboride particles generated by the reaction. The flux after adsorbing impurities floats into the slag layer and is removed in the subsequent slag removal operation.
[0018] The present invention specifically designs the composition and content of the first flux and the second flux, thereby improving the removal rate of titanium in the aluminum silicon alloy. Analysis of the reasons: Specific components in the first flux, such as sodium chloride, potassium chloride, potassium fluoride, aluminum fluoride, potassium fluoroborate, etc., can react selectively with the titanium in the aluminum silicon alloy to generate easily separable compounds, especially to form TiB2 through boration reaction. This selectivity helps to reduce the impact on other useful elements and focus on the removal of titanium. The presence of potassium fluoroborate in the first flux promotes the boration reaction of the titanium-containing phase, improves the yield of boron, and thus accelerates the conversion process of titanium to TiB2. This not only speeds up the reaction rate, but also increases the removal efficiency of titanium. Components in the second flux, such as boron oxide, sodium carbonate, etc., can interact with the TiB2 particles formed after the reaction of the first flux to form larger particles or agglomerates, which are easier to separate from the melt to form slag, thereby effectively removing titanium from the alloy. The present invention utilizes specific chemical reactions and physical separation methods to effectively remove the titanium element in the aluminum-silicon alloy melt and reduce the titanium content to an ideal range.
[0019] Preferably, in step (1), the titanium content in the titanium-aluminum-silicon alloy to be removed is 0.1-0.8%, and the silicon content is 2.5-20%.
[0020] Preferably, in step (1), the heating temperature is 690-860° C., and the inert gas is one of argon or nitrogen.
[0021] Preferably, in step (1), the preparation process of the first flux is:
[0022] Sodium chloride, potassium chloride, potassium fluoride and aluminum fluoride are mixed, smelted at 800-850°C, then cast into blocks, crushed into granules, mixed with potassium borofluoride, sodium carbonate and calcium fluoride granules, ground and sieved, and dried to obtain a first flux, the particle size of which is 0.15-2 mm.
[0023] It should also be noted that the steps of mixing sodium chloride, potassium chloride, potassium fluoride and aluminum fluoride and then smelting and casting in the preparation process of the first flux of the present invention can also be replaced by directly mixing the molten salts of sodium chloride, potassium chloride, potassium fluoride and aluminum fluoride in a powder mixer.
[0024] Preferably, in step (1), the injection amount of the first flux is 1 to 8% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
[0025] Preferably, in step (2), the stirring time is 5 to 15 minutes, the insulation temperature is 690 to 860° C., and the insulation time is 1 to 20 minutes.
[0026] Preferably, in step (3), the second flux is prepared by:
[0027] Sodium chloride, potassium chloride, potassium fluoride and potassium cryolite are mixed, smelted at 800-850°C, then cast into blocks, crushed into granules, mixed with boron oxide and sodium carbonate particles, ground and sieved, and dried to obtain a second flux, the particle size of which is 0.15-2 mm.
[0028] It should also be noted that the steps of mixing sodium chloride, potassium chloride, potassium fluoride and potassium cryolite and then smelting and casting in the preparation process of the second flux of the present invention can also be replaced by directly mixing the molten salts of sodium chloride, potassium chloride, potassium fluoride and potassium cryolite in a powder mixer.
[0029] Preferably, in step (3), the spraying amount of the second flux is 0.2 to 5% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
[0030] Preferably, the ratio of the weight percentage of sodium chloride in the first flux to the weight percentage of sodium chloride in the second flux is 0.33 to 0.43;
[0031] The ratio of the weight percentage of potassium chloride in the first flux to the weight percentage of potassium chloride in the second flux is 0.34 to 0.42;
[0032] The ratio of the weight percentage of potassium fluoride in the first flux to the weight percentage of potassium fluoride in the second flux is 0.53 to 1.23;
[0033] The ratio of the weight percentage of sodium carbonate in the first flux to the weight percentage of sodium carbonate in the second flux is 0.6 to 1.1.
[0034] The present invention can adjust the physical and chemical properties of the flux, such as melting point, viscosity, etc., by precisely controlling the ratio of various components in the first flux and the second flux, so that the flux is easier to contact and fully mix with the molten metal, thereby improving the activity of the reaction interface and enhancing the purification effect. There is a certain synergistic effect between the first flux and the second flux. The first flux is responsible for reacting with the titanium element to generate TiB2, while the second flux is mainly responsible for capturing and removing these TiB2 particles. The reasonable ratio and use order between the two ensure the effectiveness and continuity of the entire purification process.
[0035] In order to optimize the reaction parameters, improve the synergistic effect between the first flux and the second flux, and further improve the removal rate of the titanium element, the present invention also defines the ratio of the weight percentage of sodium chloride, potassium chloride, potassium fluoride and sodium carbonate in the first flux to the same components in the second flux. The present invention can optimize the balance of the chemical reaction by accurately controlling the ratio of sodium chloride, potassium chloride, potassium fluoride, sodium carbonate and other components in the first flux and the second flux, ensuring that the titanium element fully reacts with the active components in the flux to generate more TiB2 particles. In the present invention, the proportion of potassium fluoride in the first flux is relatively high, which helps to improve the selectivity of the boronization reaction of the titanium element and generate more TiB2. In the second flux, the proportion of potassium fluoride is relatively low, which helps to enhance the wettability of the flux to TiB2 particles, improve the fluidity of the flux and the separation from the melt, and maintain the cleanliness of the melt. This improvement in selectivity can ensure that the titanium element preferentially reacts with specific components in the flux and enhances the separation effect of the titanium-containing product and the melt, thereby improving the removal rate of titanium.
[0036] Preferably, the ratio of the spraying amount of the first flux to the spraying amount of the second flux is 1.3-3.
[0037] The present invention limits the injection amount of the first flux and the second flux. By controlling the ratio of the first flux to the second flux between 1.3 and 3, it can ensure that the TiB2 particles generated by the reaction of the first flux can be fully adsorbed and captured by the second flux, avoiding unreacted TiB2 particles from remaining in the melt.
[0038] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0039] 1. The present invention can effectively remove titanium in aluminum silicon alloy by using a first flux and a second flux in a specific ratio, with a removal rate of more than 70%.
[0040] 2. The purification and titanium removal process of the present invention is simple and easy to operate. It does not require major modifications to existing aluminum silicon alloy production equipment or additional equipment investment, which greatly reduces the cost burden of the enterprise.
[0041] 3. The fluxes used in the present invention are all harmless treatment substances, and the temperature conditions used in the whole process are moderate, which not only ensures the treatment effect, but also avoids the energy waste caused by high-temperature operation, which is in line with the concept of green manufacturing.
[0042] 4. The present invention has a wide application range for the initial titanium content (0.1-0.8%) and silicon content (2.5-20%) in aluminum-silicon alloys, which means that it can adapt to aluminum-silicon alloy raw materials of different sources and specifications, enhancing the application flexibility and extensiveness of the process. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 is the alloy metallographic diagram of Example 1;
[0044] Figure 2 is the alloy metallographic diagram of Example 2;
[0045] Figure 3 is the alloy metallographic diagram of Example 5;
[0046] Figure 4 This is the alloy metallographic diagram of Comparative Example 6. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Example 1
[0049] This embodiment provides a process for purifying and removing titanium from an aluminum-silicon alloy flux, comprising the following steps:
[0050] (1) Preparation of refining agent
[0051] The first flux comprises the following components by weight percentage:
[0052] 10% sodium chloride, 13% potassium chloride, 10% potassium fluoride, 11% aluminum fluoride, 35% potassium fluoroborate, 11% sodium carbonate, 10% calcium fluoride;
[0053] The preparation process of the first flux is:
[0054] Sodium chloride, potassium chloride, potassium fluoride and aluminum fluoride are mixed, smelted at 825°C, then cast into blocks, crushed into granules, mixed with potassium borofluoride, sodium carbonate and calcium fluoride particles, ground and sieved, and dried to obtain a first flux, the particle size of which is 0.18 mm.
[0055] The second flux comprises the following components by weight percentage:
[0056] 24% sodium chloride, 32% potassium chloride, 10% potassium fluoride, 7% potassium cryolite, 13% boric oxide, 14% sodium carbonate;
[0057] The preparation process of the second flux is as follows:
[0058] Sodium chloride, potassium chloride, potassium fluoride and potassium cryolite are mixed, smelted at 825°C, then cast into blocks, crushed into granules, mixed with boron oxide and sodium carbonate particles, ground and sieved, and dried to obtain a second flux, the particle size of which is 0.18 mm.
[0059] (2) heating the titanium-aluminum-silicon alloy to be removed at 705° C. until it is uniformly melted to obtain a melt, and spraying a first flux into the melt using an inert gas, argon, to perform a first flux spraying process;
[0060] The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.2% and the silicon content is 5%;
[0061] The injection amount of the first flux is 2% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
[0062] (3) After the first flux is sprayed, the melt is stirred and kept warm and allowed to stand;
[0063] The stirring method is mechanical propeller stirring, the stirring time is 10 minutes, the insulation temperature is 705°C, and the insulation time is 10 minutes.
[0064] (4) After the melt is kept at a temperature and allowed to stand, the second flux is sprayed with inert gas argon to perform a second flux spraying process;
[0065] The injection amount of the second flux is 1% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
[0066] (5) After the second flux is sprayed, the flux slag on the surface of the melt is scraped off to obtain an aluminum-silicon alloy melt.
[0067] (6) The obtained aluminum-silicon alloy melt is temperature-controlled and allowed to stand at 700° C. for 15 minutes. After stirring, filtering and casting, a pure aluminum-silicon alloy is obtained after titanium is removed.
[0068] The titanium content of the aluminum-silicon alloy after purification in this embodiment is 0.05%.
[0069] Alloy structure Figure 1 As shown, Figure 1 The middle black is the Al matrix, and the light grey flake phase is the Si-rich phase. Due to the removal of the titanium element, the image does not contain the coarse needle-like Al3Ti phase commonly found in high-titanium aluminum-silicon alloys.
[0070] Example 2
[0071] The method of this embodiment is the same as that of embodiment 1, except that:
[0072] (1) The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.3% Ti and the silicon content is 8%.
[0073] (2) The components of the first flux are as follows by weight: 9% sodium chloride, 12% potassium chloride, 9% potassium fluoride, 10% aluminum fluoride, 40% potassium fluoroborate, 12% sodium carbonate, and 8% calcium fluoride; the injection amount of the first flux is 3% of the total weight of the aluminum-silicon alloy melt.
[0074] (3) The components of the second flux are as follows by weight: 23% sodium chloride, 30% potassium chloride, 11% potassium fluoride, 8% potassium cryolite, 14% boric oxide, and 14% sodium carbonate; the injection amount of the second flux is 2% of the total weight of the aluminum-silicon alloy melt.
[0075] (4) The heating melting temperature and the holding temperature are both 720°C, and the mixture is kept at this temperature for 9 minutes.
[0076] The titanium content of the aluminum-silicon alloy after purification in this embodiment is 0.06%.
[0077] Alloy structure Figure 2 As shown, the figure does not contain the coarse needle-shaped Al3Ti phase commonly found in high titanium aluminum silicon alloys.
[0078] Example 3
[0079] The method of this embodiment is the same as that of embodiment 1, except that:
[0080] (1) The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.4% Ti and 10% silicon.
[0081] (2) The components of the first flux are as follows by weight percentage: 8% sodium chloride, 11% potassium chloride, 8% potassium fluoride, 9% aluminum fluoride, 45% potassium fluoroborate, 13% sodium carbonate, and 6% calcium fluoride; when preparing the first flux, sodium chloride, potassium chloride, potassium fluoride, and aluminum fluoride are not melted, but directly mixed as molten salt. The injection amount of the first flux is 4% of the total weight of the aluminum-silicon alloy melt.
[0082] (3) The components of the second flux are as follows by weight percentage: 22% sodium chloride, 28% potassium chloride, 12% potassium fluoride, 9% potassium cryolite, 15% boron oxide, and 14% sodium carbonate; when preparing the second flux, sodium chloride, potassium chloride, potassium fluoride, and potassium cryolite are not melted but directly mixed as molten salt. The injection amount of the second flux is 3% of the total weight of the aluminum-silicon alloy melt.
[0083] (4) The heating melting temperature and the holding temperature are both 735°C, and the mixture is kept at this temperature for 13 minutes.
[0084] The titanium content of the aluminum-silicon alloy after purification in this embodiment is 0.08%.
[0085] Example 4
[0086] The method of this embodiment is the same as that of embodiment 1, except that:
[0087] (1) The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.6% Ti and the silicon content is 12%.
[0088] (2) The components of the first flux are as follows by weight: 7% sodium chloride, 10% potassium chloride, 7% potassium fluoride, 8% aluminum fluoride, 48% potassium fluoroborate, 15% sodium carbonate, and 5% calcium fluoride; the injection amount of the first flux is 6% of the total weight of the aluminum-silicon alloy melt.
[0089] (3) The components of the second flux are as follows by weight: 21% sodium chloride, 27% potassium chloride, 12.5% potassium fluoride, 9.5% potassium cryolite, 15% boric oxide, and 15% sodium carbonate; the injection amount of the second flux is 4% of the total weight of the aluminum-silicon alloy melt.
[0090] (4) The heating melting temperature and the holding temperature are both 750°C, and the mixture is kept at this temperature for 17 minutes.
[0091] The titanium content of the aluminum-silicon alloy after purification in this embodiment is 0.1%.
[0092] Example 5
[0093] The method of this embodiment is the same as that of embodiment 1, except that:
[0094] (1) The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.8% Ti and the silicon content is 20%.
[0095] (2) The components of the first flux are as follows by weight percentage: 7% sodium chloride, 9% potassium chloride, 7% potassium fluoride, 8% aluminum fluoride, 50% potassium fluoroborate+, 16% sodium carbonate, and 3% calcium fluoride; when preparing the first flux, sodium chloride, potassium chloride, potassium fluoride, and aluminum fluoride are not melted, but directly mixed as molten salt. The injection amount of the first flux is 8% of the total weight of the aluminum-silicon alloy melt.
[0096] (3) The components of the second flux are as follows by weight percentage: 20% sodium chloride, 26% potassium chloride, 13% potassium fluoride, 10% potassium cryolite, 16% boron oxide, and 15% sodium carbonate; when preparing the second flux, sodium chloride, potassium chloride, potassium fluoride, and potassium cryolite are not melted but directly mixed as molten salt. The injection amount of the second flux is 5% of the total weight of the aluminum-silicon alloy melt.
[0097] (4) The heating melting temperature and the holding temperature are both 860°C, and the mixture is kept at this temperature for 20 minutes.
[0098] The titanium content of the purified aluminum-silicon alloy in this embodiment is 0.15%. Figure 3 As shown, the figure does not contain the coarse needle-shaped Al3Ti phase commonly found in high titanium aluminum silicon alloys.
[0099] Comparative Example 1
[0100] The method of this comparative example is the same as that of Example 2, except that:
[0101] (1) The titanium content of the titanium-aluminum-silicon alloy to be removed is 0.1% Ti and the silicon content is 2.5%.
[0102] (2) The components of the first flux are as follows by weight percentage: 11% sodium chloride, 14% potassium chloride, 11% potassium fluoride, 12% aluminum fluoride, 30% potassium fluoroborate, 8% sodium carbonate, and 14% calcium fluoride; when preparing the first flux, sodium chloride, potassium chloride, potassium fluoride, and aluminum fluoride are not melted, but directly mixed as molten salt. The injection amount of the first flux is 1% of the total weight of the aluminum-silicon alloy melt.
[0103] (3) The components of the second flux are as follows by weight percentage: 26% sodium chloride, 34% potassium chloride, 9% potassium fluoride, 6% potassium cryolite, 12% boron oxide, and 13% sodium carbonate; when preparing the second flux, sodium chloride, potassium chloride, potassium fluoride, and potassium cryolite are not melted but directly mixed as molten salt. The injection amount of the second flux is 1% of the total weight of the aluminum-silicon alloy melt.
[0104] (4) The heating melting temperature and the holding temperature are both 690°C, and the mixture is kept at this temperature for 1 minute.
[0105] The titanium content of the purified aluminum-silicon alloy in this comparative example is 0.05%.
[0106] Comparative Example 2
[0107] The difference between this comparative example and Example 2 is that the added amounts of sodium chloride and potassium chloride in the second flux are different. In this comparative example, the weight percentage of sodium chloride in the second flux is 35%, and the weight percentage of potassium chloride is 18%.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 2 is that the addition amounts of potassium chloride and potassium fluoride in the second flux are different. In this comparative example, the weight percentage of potassium chloride in the second flux is 21%, and the weight percentage of potassium fluoride is 20%.
[0110] Comparative Example 4
[0111] The difference between this comparative example and Example 2 is that the added amounts of potassium fluoroborate and sodium carbonate in the first flux are different. In this comparative example, the weight percentage of potassium fluoroborate in the first flux is 33%, and the weight percentage of sodium carbonate is 5%.
[0112] Comparative Example 5
[0113] The difference between this comparative example and Example 2 is that the injection amount of the second flux is different. In this comparative example, the injection amount of the second flux is 0.5% of the total weight of the aluminum-silicon alloy melt.
[0114] Comparative Example 6
[0115] The difference between this comparative example and Example 2 is that the first flux spraying process and the second flux spraying process are not performed, and the titanium content of the aluminum-silicon alloy melted in this comparative example is 0.3%. Figure 4 As shown in the figure, the black is the Al matrix, the light gray is the Si-rich phase, and the white coarse needle-like phase is the Al3Ti phase. Because the titanium content is high, the figure contains more coarse needle-like Al3Ti phases commonly found in high-titanium aluminum-silicon alloys.
[0116] Element content test
[0117] Titanium removal rate = (initial titanium content in the titanium aluminum silicon alloy to be removed - titanium content in the aluminum silicon alloy after purification) / initial titanium content in the titanium aluminum silicon alloy to be removed × 100. The titanium removal rates of the embodiments and comparative examples are shown in Table 1.
[0118] Table 1 Element content test results
[0119] Initial titanium content% Titanium content after purification % Titanium removal rate% Example 1 0.2 0.05 75 Example 2 0.3 0.06 80 Example 3 0.4 0.08 80 Example 4 0.6 0.1 83.33 Example 5 0.8 0.15 81.25 Comparative Example 1 0.1 0.05 50 Comparative Example 2 0.3 0.14 63.33 Comparative Example 3 0.3 0.1 69.67 Comparative Example 4 0.3 0.12 60 Comparative Example 5 0.3 0.16 46.67 Comparative Example 6 0.3 0.3 0
[0120] It can be seen from the above performance test results that the titanium removal effect of Examples 1-5 is good, especially the comprehensive performance of Example 4 is the most outstanding. This is mainly because the present invention uses a unique method of spraying the first flux and the second flux separately. The first flux is a boron-containing molten salt, which performs boronization of the titanium-containing phase and promotes the improvement of the boron element recovery rate. The second flux adsorbs the TiB2 particles after the reaction, prompting the titanium-containing particles to enter the slag layer. The spraying interval and stirring operation of the first flux and the second flux promote the full boronization reaction of the titanium-containing phase.
[0121] However, the comparative example is obviously inferior to the embodiment in the corresponding performance test because it does not adopt the necessary technical solution. In comparative example 1, the addition ratio of the first flux and the second flux is changed, and it can be seen that the titanium removal rate of the aluminum silicon alloy decreases, proving that the addition ratio of the first flux and the second flux has an important influence on the titanium removal rate. In comparative example 2, the weight percentage of sodium chloride and potassium chloride in the second flux is changed, resulting in the ratio of the weight percentage of sodium chloride in the first flux to the weight percentage of sodium chloride in the second flux, and the ratio of the weight percentage of potassium chloride in the first flux to the weight percentage of potassium chloride in the second flux exceeds the range defined by the present invention. From the results, it can be seen that the titanium removal rate of the aluminum silicon alloy decreases by using the same process method, indicating that the first flux and the second flux have a synergistic effect. In comparative example 3, the weight percentage of potassium chloride and potassium fluoride in the second flux is changed, which also makes the ratio of the weight percentage of raw materials between the two fluxes exceed the range defined by the present invention. Using the same process method, the titanium removal rate of the aluminum silicon alloy decreases, which also shows that the first flux and the second flux have a synergistic effect. In Comparative Example 4, the weight percentage of sodium carbonate in the first flux was changed, resulting in the ratio of the weight percentage of sodium carbonate in the two fluxes exceeding the range specified in the present invention, and the removal rate of titanium in the aluminum silicon alloy decreased, indicating that the limitation of the weight percentage ratio of the raw materials in the two fluxes in the present invention has a very important influence on the comprehensive improvement of the titanium removal rate of the aluminum silicon alloy. In Comparative Example 5, the injection amount of the second flux was reduced, which was lower than the injection amount of the first flux. From the results, it can be seen that the removal rate of titanium in the aluminum silicon alloy decreased, indicating that the specific limitation of the injection amount ratio of the first flux and the second flux in the present invention has an important influence on the comprehensive improvement of the titanium removal rate. In Comparative Example 6, the first flux and the second flux were not added. From the results, it can be seen that the titanium element in the aluminum silicon alloy cannot be removed, indicating the necessity of using the first flux and the second flux in the present invention. The above experimental results further prove the importance of the technical scheme defined in the present invention for its technical effect.
[0122] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A process for purifying and removing titanium from aluminum-silicon alloy flux, characterized in that: The following steps are involved: (1) heating the titanium-aluminum-silicon alloy to be removed until it is uniformly melted to obtain a melt, and spraying a first flux into the melt using an inert gas to perform a first flux spraying process; The first flux comprises the following components by weight percentage: 7-11% sodium chloride, 9-14% potassium chloride, 7-11% potassium fluoride, 8-12% aluminum fluoride, 30-50% potassium fluoroborate, 8-16% sodium carbonate, 3-14% calcium fluoride; (2) After the first flux is sprayed, the melt is stirred and kept warm and allowed to stand; (3) After the melt is kept at a temperature and allowed to stand, an inert gas is used to spray a second flux, and a second flux spraying process is performed; The second flux comprises the following components by weight percentage: 20-26% sodium chloride, 26-34% potassium chloride, 9-13% potassium fluoride, 6-10% potassium cryolite, 12-16% boric oxide, 13-15% sodium carbonate; (4) After the second flux is sprayed, the flux slag on the surface of the melt is scraped off to obtain an aluminum-silicon alloy melt; (5) The obtained aluminum-silicon alloy melt is temperature-controlled and allowed to stand, stirred, filtered and cast to obtain a pure aluminum-silicon alloy after titanium is removed.
2. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (1), the titanium content in the titanium-aluminum-silicon alloy to be removed is 0.1-0.8%, and the silicon content is 2.5-20%.
3. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (1), the heating temperature is 690-860° C., and the inert gas is one of argon and nitrogen.
4. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (1), the preparation process of the first flux is: Sodium chloride, potassium chloride, potassium fluoride and aluminum fluoride are mixed, smelted at 800-850°C, then cast into blocks, crushed into granules, mixed with potassium borofluoride, sodium carbonate and calcium fluoride granules, ground and sieved, and dried to obtain a first flux, the particle size of which is 0.15-2 mm.
5. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (1), the spraying amount of the first flux is 1 to 8% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
6. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (2), the stirring time is 5 to 15 minutes, the insulation temperature is 690 to 860° C., and the insulation time is 1 to 20 minutes.
7. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (3), the preparation process of the second flux is as follows: Sodium chloride, potassium chloride, potassium fluoride and potassium cryolite are mixed, smelted at 800-850°C, then cast into blocks, crushed into granules, mixed with boron oxide and sodium carbonate particles, ground and sieved, and dried to obtain a second flux, the particle size of which is 0.15-2 mm.
8. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: In step (3), the spraying amount of the second flux is 0.2 to 5% of the weight of the titanium-aluminum-silicon alloy melt to be removed.
9. The process for purifying and removing titanium from aluminum-silicon alloy flux according to claim 1, characterized in that: The ratio of the weight percentage of sodium chloride in the first flux to the weight percentage of sodium chloride in the second flux is 0.33 to 0.43; The ratio of the weight percentage of potassium chloride in the first flux to the weight percentage of potassium chloride in the second flux is 0.34 to 0.42; The ratio of the weight percentage of potassium fluoride in the first flux to the weight percentage of potassium fluoride in the second flux is 0.53 to 1.23; The ratio of the weight percentage of sodium carbonate in the first flux to the weight percentage of sodium carbonate in the second flux is 0.6 to 1.
1.
10. A process for purifying and removing titanium from aluminum-silicon alloy flux according to any one of claims 5 or 8, characterized in that: The ratio of the spraying amount of the first flux to the spraying amount of the second flux is 1.3-3.
Citation Information
Patent Citations
Method for adjusting content of titanium element in aluminum-silicon alloy melt
CN116287799A